(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
In the epic "Layli and Majnun", which is the third epic of the great writer Alisher Navoi’s "Khamsa", terms related to various sciences and professions of his time were used. In particular, terms related to the social, political, military, animal and plant world, related to the science of astrology (astronomy), meaning medical, musical, mineral names, related to various sciences and professions, related to religious concepts, to Terms related to ’y and mourning rites and several terms related to many other fields are skillfully used in the work. In this article, we will discuss the semantic features of the terms used in this epic. The lexical-semantic phenomena appearing in the current Uzbek terminology and the semantic features characteristic of language units in general have been studied with the help of distributive and transformational analysis methods.